2022
DOI: 10.1007/s10346-021-01810-6
|View full text |Cite
|
Sign up to set email alerts
|

Geological and soil engineering properties of shallow landslides occurring in the Kutupalong Rohingya Camp in Cox’s Bazar, Bangladesh

Abstract: The Forcibly Displaced Myanmar Nationals (FDMN), historically known as ‘Rohingya’ who fled the 2017 ethnic atrocities and genocide in the Northern Rakhine State of Myanmar, took shelter in Cox’s Bazar District of Bangladesh. The camp network, known as Kutupalong Rohingya Camp (KRC), is situated in the tectonically active tertiary hilly terrain. The KRC has been experiencing hydrometeorological hazards, where landslides are frequent. This study investigated the slopes’ geological condition, engineering properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Other essential factors triggering landslides in the region are rock types or lithology, age of the rocks, degree of weathering, and presence of weak zones and fissile shales. The rock types of the hills in CHD are primarily composed of sandstone, siltstone, and shale (Kamal et al 2022). Among them, sandstone grains are explicitly susceptible to coarse landslides and have more porosity and permeability.…”
Section: Study Area Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Other essential factors triggering landslides in the region are rock types or lithology, age of the rocks, degree of weathering, and presence of weak zones and fissile shales. The rock types of the hills in CHD are primarily composed of sandstone, siltstone, and shale (Kamal et al 2022). Among them, sandstone grains are explicitly susceptible to coarse landslides and have more porosity and permeability.…”
Section: Study Area Profilementioning
confidence: 99%
“…Thus, focusing on anthropogenic activities of landslide disasters is an essential aspect of developing a comprehensive and inclusive DRR strategy. Existing literature primarily focuses on the geomorphology, lithology, rainfall pattern and slope engineering perspectives (Kamal et al 2022). Still, there is a severe lack of exploring the anthropogenic aggravation of landslide disasters in CHD, especially from an expert's point of view.…”
Section: Introductionmentioning
confidence: 99%
“…The term forensic geology here refers to an investigation of geological conditions to determine the cause or physical evidence of landslides that occur in a specific area from the geological point of view. Several studies on the geological conditions of various landslide events, such as those in Mendatica, Tianquan, and Kutupalong, Rohingya, have been conducted [26][27][28]. The factors affecting landslides are topography, geology, climate, land use, environmental conditions, rainwater infiltration, and surface water flow.…”
Section: Geology and Environmentmentioning
confidence: 99%
“…The grain size analysis of the collected landslide slope materials from the field was done in the laboratory by a combined hydrometer and mechanical sieve analysis following the ASTM standards. In addition, detailed information on shear strength and other engineering parameters of soils in the KRC were collected from Kamal et al (2022).…”
Section: Particle Size Distributionmentioning
confidence: 99%
“…After the settlement of Rohingya refugees, extensive deforestation and slope cutting eventually resulted in numerous landslide occurrences (Braun et al 2019;Hasan et al 2020;Hossain and Moniruzzaman 2021). Kamal et al (2022) showed that anthropogenic interventions and low strength of residual soil are the major causes of landslide occurrence in the KRC. The large scarp of slope washed away with a massive volume of materials during the 27 July 2021 landslide event directly buried some houses on the modified slope and completely/partially destroyed them.…”
Section: Introductionmentioning
confidence: 99%